‘I Get High With a Little Help From My Friends’ - How Raves Can Invoke Identity Fusion and Lasting Co-operation via Transformative Experiences - Newson, Martha; Khurana, Ragini; Cazorla, Freya; van Mulukom, Valerie (Frontiers in Psychology, 2021)
Psychoactive drugs have been central to many human group rituals throughout modern human evolution. Despite such experiences often being inherently social, long-term social bonding has rarely been empirically tested as an outcome. Here we investigate a novel measure of the mechanisms that generate altered states of consciousness during group rituals, the 4Ds: dance, drums, sleep deprivation, and drugs. We conducted an online survey retrospectively examining experiences at a highly ritualised cultural phenomenon where drug use is relatively uninhibited- raves and illegal free parties (n=481). Engaging in the 4Ds at raves or free parties led to personal transformation for those who experienced the event as liminal or awe-inspiring, especially for people with open personalities. Without liminality, or a ritual context, indulging in the 4Ds was associated with a lack of personal growth, or anomie. Personal transformation following awe-inspiring raves was associated with long-term bonding to a local group (other ravers) and prosocial behaviour towards this group at a cost to self in a simple economic game. Bonding to an extended group (humanity) was not associated with these events. The findings suggest that employing the 4Ds in a ritualised environment - particularly dancing and drug use – can help build lasting, meaningful social bonds with associated positive behavioural outcomes.